Micro-Scale Approach in Organic Chemistry Learning as an Innovative Strategy to Support Sustainable Development Goals (SDGS) - Rohiat, Salastri; Rochintaniawati, Diana; Riandi (Journal of Tropical Chemistry Research and Education, 2025)
The micro-scale approach in organic chemistry learning offers an innovative solution to enhance the effectiveness of the teaching and learning process while supporting the Sustainable Development Goals (SDGs). This study aims to describe the implementation of the micro-scale approach in the curriculum of an organic chemistry course at a higher education institution. This approach emphasizes the use of small quantities of chemicals, simple laboratory equipment, and eco-friendly techniques to minimize laboratory waste, operational costs, and negative environmental impacts. The research method involves qualitative analysis to evaluate the effectiveness of this approach in terms of learning outcomes and its relevance to the SDGs, particularly those related to quality education. The results reveal that the micro-scale approach has not yet been implemented in organic chemistry learning. However, organic chemistry lecturers and students have a general understanding of the concept of the micro-scale approach. Moreover, both lecturers and students recognize that the micro-scale concept aligns with the objectives of sustainable development. This study concludes that the micro-scale approach is an innovative and effective strategy to support sustainability-oriented organic chemistry learning. The implementation of this approach is expected to serve as a replicable learning model across various educational institutions, contributing to broader SDGs achievements